Politeness Strategies Used in the Discussion of Covid-19 Vaccine's in Quora Accounts - Octarina, Melani (Journal of Literature, Linguistics, & Cultural Studies, 2023)
Everyone may participate in online discussions in this digital age. One of the platforms they can use is Quora. They exchanged their ideas and got information from other users on the COVID-19 vaccine controversy, which has been widely discussed since the epidemic. They can reveal (real account) or conceal (anonymous account) their identity. Then, to avoid debate between users, speakers must use politeness strategies adapted to CMC. This study aims to identify differences in politeness between real/non-anonymous and anonymous in the comments column on Quora in discussions about the Covid-19 vaccine controversy. This research is included in the descriptive qualitative research with a pragmatic approach used to describe linguistic data related to the forms of politeness strategies found in the analysis. Then, the data were taken from netizens’ comments on the five discussions users most discussed from January 2021 to September 2022. The researcher used the theory of Brown and Levinson (1987), which has been adjusted by Nikzam (2013) and Park (2008), to analyze data on the CMC context. This study found that the most widely used politeness strategies were negative ones, followed by positive politeness, off-record, and bald-on record. However, the researcher also found that speakers use linguistic devices to convey interpersonal and affective attitudes in online communication. The tools used are abbreviations and emoticons that aim to simulate gestures and facial expressions (Park, 2008). Further research is needed to determine politeness in CMC (Computer-Mediated Communication) on different discussion platforms.